BERTAHAN DI TENGAH PERGULATAN ZAMAN (Kajian Sejarah Sosial-Ekonomi Komunitas Keturunan Hadrami di Yogyakarta Abad Ke-20) - Fatiyah . (Thaqafiyyat : Jurnal Bahasa, Peradaban dan Informasi Islam, 2012)
The community development of the Hadrami (jamaah) in Yogyakarta in the 20th was not separated from the life construction of the former Hadrami generation. All social process and experiences have influenced their point of view and dynamism going on the community social life in Yogyakarta. In social context, the Hadrami generation of Yogyakarta who were born in the early 20th century has been the "becoming Java" generation or even have never "been Arab" before. The nature surrounded by Javanese culture values and the nurture under the care of a noble- family mother tended to make the Arab descendant to know the mother's culture rather than the father's. This contribution that caused much identity disorientation or dilemma experienced by lots of Hadrami in Yogyakarta. The phenomenon appears when the interaction process is going on with the Arab new comers from other cities starting in 1940's. Besides that, they also gave the contribution in birth of economic activities among the Hadrami of Yogyakarta.The existence of Arab community in Yogya is also influenced by symbols belonged to the community in the middle of the Yogya society. Besides that, the division of history into period to reveal the existence of jamaah is in fact very decisive in coloring the life dynamism and change in the community. Therefore, the two period’s phases consisting of the arrival period and the social-economic condition period are expected to be able to interpret the reality of the change process happening and survival forms to the Hadrami people in Yogyakarta in the 20th century.